ANALYSIS OF INDONESIAN COMMITMENT PRINCIPLES IN THE G20 ANTI-CORRUPTION WORKING GROUP IN 2020 - Beni Sukri; Nurainun; Rustam Rustam (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
Corruption is an act that violates the law, and this act often occurs in every country in the world, including Indonesia. Currently, the state has begun to realize the dangers caused by acts of corruption that can harm various fields such as economic, social and political in a country. With many countries experiencing the problem of corruption, there is a desire to jointly eradicate it by holding a joint agreement and committing to overcome it. The implementation of the G20 Anti-Corruption Working Group activity in 2020 is a continuation of previous activities to declare a joint commitment to fighting corruption. The Government of Indonesia through the Ministry of Foreign Affairs strives to always play an active role in these activities. The purpose of this paper is to analyze the principles contained in the commitments agreed by the countries participating in the G20 Anti-Corruption Working Group in 2020. The method used in writing this article is normative juridical or can also be called doctrinal legal research. This paper uses secondary data. Secondary data is data obtained by an organization or individual from other parties who have collected and obtained it before. The results obtained from this paper are that there are principles agreed upon in the G20 Anti-Corruption Working Group in 2020, namely: 1) principles for the preparation and implementation of a national strategy on anti-corruption; 2) principles to Promote Integrity in Privatization and Public-Private Partnerships; 3) the principle of Encouraging the Integrity of the Public Sector through the Use of Information and Communication Technology.